Cerebrospinal fluid oxygen optimisation for rescue of metabolically challenged in vitro cortical brain tissue. (December 2020) - Voss, Logan J.; Whittle, Nicola; Lamber, Oliver; Envall, Gustav; Sleigh, Jamie
Highlights: Cerebrocortical hypoxia-ischemia can be simulated in mouse cortical slices. Tissue recovery is maximised by optimising the dissolved oxygen levels in the artificial cerebrospinal fluid. Supplementing dissolved oxygen with oxygen nanobubbles does not support improved tissue recovery. Oxygen in nanobubble form is not biologically available to cortical tissue. Abstract: Hypoxic-ischaemic brain injury is a major cause of morbidity and mortality internationally. Using an in vitro isolated cortex model, this study investigated the optimal cerebrospinal fluid oxygenation parameters for rescuing metabolically challenged cortical tissue. In particular, we asked whether maximizing oxygen content with oxygen nanobubbles could support improved tissue recovery. Mouse cortical slices were metabolically starved, followed by recovery in artificial cerebrospinal fluid (aCSF) containing different levels of dissolved oxygen ranging from mean(SD) 2(0.5) to 39(1.0) mg/L; with and without oxygen nanobubbles. Tissue recovery was assessed by quantifying and comparing the amplitude, length, high frequency content and event frequency of seizure-like events generated in no-magnesium aCSF at the beginning and end of the protocol. In general, there was improved recovery with increasing oxygen content up to 25–34 mg/L. The outcome of slices recovered in nanobubbled aCSF was no different to conventionally oxygenated slices with similar dissolved oxygen content. Dissolved oxygen content above 34 mg/L afforded no additional benefit. In conclusion, aCSF dissolved oxygen content of approximately 30 mg/L is optimal for cortical tissue recovery from metabolic starvation, which is easily achievable using conventional oxygenation methods. Oxygen in the form of nanobubbles does not appear to be readily available for tissue oxidative processes in this model.